Neuroanatomical Alterations in Tinnitus Assessed with Magnetic Resonance Imaging - Allan, Thomas W.; Besle, Julien; Langers, Dave R. M.; Davies, Jeff; Hall, Deborah A.; Palmer, Alan R.; Adjamian, Peyman (Frontiers in Aging Neuroscience, 2016)
Previous studies of anatomical changes associated with tinnitus have provided inconsistent results, with some showing significant cortical and subcortical changes, while others have found effects due to hearing loss, but not tinnitus. In this study, we examined changes in brain anatomy associated with tinnitus using anatomical scans from 128 participants with tinnitus and hearing loss, tinnitus with clinically normal hearing, and non-tinnitus controls with clinically normal hearing. The groups were matched for hearing loss, age, and gender. We employed voxel- and surface-based morphometry to investigate grey and white matter volume and thickness within regions-of-interest that were based on the results of previous studies. Analysis of regions of interest revealed numerous increases and decreases in grey matter and thickness between tinnitus and non-tinnitus controls, in various cortical and subcortical structures. For whole brain analysis, the main tinnitus-related significant clusters were found outside sensory auditory structures. Overall, while some of the morphological differences observed in this study are similar to previously published findings, others are entirely different or even contradict previous results. We highlight other discrepancies among previous results and the increasing need for a more precise subtyping of the condition.